(untitled) (Molecular Medicine Communications, 2023)
Degenerative Hepatocellular carcinoma (HCC) is one of the leading causes of cancer-related deaths worldwide, with surgical resection followed by chemotherapy being the primary treatment method. However, the complex nature and high metastatic potential of HCC often render treatment plans ineffective, and acquired drug resistance frequently results in disease relapse in patients. In this review, we conducted an extensive literature search of different databases, including Medline, Scopus, and Cochrane, to identify studies that have addressed chemoresistance in HCC. This article provides a comprehensive knowledge of molecular mechanisms of chemoresistance in HCC, including genetic polymorphism, apoptosis, DNA methylation, tumor suppressor genes, DNA repair, topoisomerases, drug efflux, and epithelial-mesenchymal transition. Understanding these mechanisms is crucial for developing personalized combination therapies, identifying chemosensitive populations, and evaluating the effectiveness of chemotherapeutic agents through cell culture and orthotopic models. Therapies that can counter these resistance mechanisms need to be developed to better manage and control the disease. This would increase the patient survival rate and help decrease the use of multiple chemotherapeutic agents that greatly increase the risk of toxicities encountered by patients. Further studies are needed, so a combined effort by healthcare professionals and pharmaceutical companies can be the key to combatting the ever-rising rate of chemoresistance in HCC.